CHATBOT IS MY BUDDY: THE ROLE OF CHATBOT AS HUMAN FRIEND IN DAILY LIFE - Dwi Hardani Oktawirawan (International Journal Labs, 2022)
Today's social relations can be done by someone both offline and online. Online social relationships can not only be woven with fellow humans. Chatbot as a form of artificial intelligence continues to develop various skills that resemble humans. This study aims to understand the use of chatbots as friends in human life, especially focusing on the advantages and limitations. The method used is a literature review that involves 10 articles about chatbots as human friends from the user's point of view. Article databases used in this review are ScienceDirect, SpringerLink, Emerald Insight, and ProQuest Research Library. Chatbots are friends with various conveniences such as being easily accessible by anyone, anytime, and anywhere. Chatbots are considered to have various emotional skills that can understand their users without judgment. The weakness of chatbots is the potential for failure to understand users' talk. Chatbots can act as everyday friends when there are no human friends to contact with